Improving Argumentation Skills Through The Application Of The Argument-Driven Inquiry Model Used By Bubble Card - Noviyana, Dyah Kirani; Mursidik, Elly’s Mersina; Sujianti, Reni (Jurnal Impresi Indonesia, 2024)
The low quality of learning that occurs in grade IV of Public Elementary Schools in Madiun can be seen from students' lack of active involvement in learning activities and learning outcomes that could be more optimal. Therefore, this study aims to improve the quality of learning by implementing more effective strategies that can motivate students to be more active and involved in the teaching and learning process. This study uses a Classroom Action Research (CAR) approach with a two-cycle design involving 23 grade IV students, ten girls and 13 boys. Data collection techniques were carried out through observation, interviews, and documentation, while the data were analyzed descriptively and qualitatively. The study's results showed a significant increase in student involvement during the learning process. Students participated more actively in group discussions and class activities and showed increased learning outcomes. This study implies that implementing more interactive learning strategies and active involvement of students can improve the quality of learning in the classroom, which is expected to be applied by other teachers to improve the quality of education in elementary schools.